Ayurveda Inspired Discovery and Development of New Drugs for Diabetes, Arthritis and Cancer - Biswajit Nag; Shayal Chandra; Hee Jee Yoon; Ganeshreddy Venumbaka; Atharva Sonune; Ananda Sen (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Renoval Innovations Inc. is utilizing its own creative library of natural product molecules, including Indian Ayurvedic ingredients, to create molecular target-based drug candidates to treat chronic diseases. Using algorithms and SAR chemistry, the company has developed and synthesized > 100 new patented molecules. Creative orally active molecules are in clinical development stages in two major health conditions: Metabolic Syndrome and Inflammation. The lead candidate for metabolic syndrome was designed to bind Insulin receptors (IR) and as the inhibitor of Protein Tyrosine Phosphatase 1B (PTP1B). The synthesized small molecule (Mw > 500 Dalton) has a binding affinity with insulin receptors and induces a cascade of signaling pathways mediated by insulin binding to IR to combat insulin resistance. The second molecule is an anti-inflammatory lead candidate that regulates proinflammatory cytokines such as TNF-a, IL-1b, and IL-6. Both molecules have passed rodent and dog GLP studies with high therapeutic index, and have entered in US-FDA standard Phase I clinical trials. In addition in our oncology drug design, >20 natural product based creative compounds were screened against 60 different human carcinoma cell lines for the selection of several lead anti-cancer molecules. Two such new cancer molecules are in preclinical stages of development. Using natural product inspired drug discovery platform, Renovel is at the forefront of discovering new class of molecules for major chronic health conditions.